Life Satisfaction and Care Burden of Caregivers Who Provide Care at Home to Elderly Patients and the Influencing Factors. - IŞIK, Kevser; ERCİ, Behice (Turkiye Klinikleri Journal of Nursing Sciences, 2018)
Objective: This study aimed to determine the relationship between life satisfaction and care burden in those who provide care to impaired elderly individuals at home and the factors that affect that relationship. Material and Methods: This relational descriptive study was conducted between July 2012 and June 2013. The study population comprised 200 caregivers who provided care to elderly individuals (aged 65 years or older) registered with the Home Care Center of Adiyaman University Training and Research Hospital. In total, 160 caregivers participated in this study. Data were collected using a questionnaire prepared by the investigator that included demographic information, the Burden Interview and the Satisfaction with Life Scale. Data were evaluated using the Statistical Program for Social Sciences (SPSS) 16.0 package program. Statistical analysis was used to number, percentage, t-test, ANOVA and correlation. Results: The majority of caregivers were women and married. Overall, the caregivers' care burden and life satisfaction were determined at moderate levels (46.45±15.40 score). Factors such as sex, income status and care satisfaction affected care burden, whereas education level and income status affected life satisfaction. A negative correlation was found between care burden and life satisfaction of the caregivers. Conclusion: The results of this study demonstrated that the burden of care decreases the life satisfaction. To decrease care burden and increase the life satisfaction of caregivers, national policies and training programmes should be developed.